2014
DOI: 10.1111/ecca.12078
|View full text |Cite
|
Sign up to set email alerts
|

Age‐biased Technical and Organizational Change, Training and Employment Prospects of Older Workers

Abstract: We analyse the role of training in mitigating the negative impact of technical and organizational changes on the employment prospects of older workers. Using a panel of French firms in the late 1990s, we first estimate wage bill share equations for different age groups. As a second step, we estimate the impact of ICT, innovative work practices and training on employment flows by age group in the next period. Training appears to have a positive impact on the employability of older workers, but it offers limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 21 publications
1
29
0
3
Order By: Relevance
“…In this vein, there is also a literature that focuses on how older workers are affected by new technologies. Most confirm that older workers make less use of ICT or computers (Friedberg, 2003;Schleife, 2006;de Koning and Gelderblom, 2006), but evidence on how their labor market outcomes are affected is mixed (Borghans and ter Weel, 2002;Aubert et al, 2006;Schleife, 2006;Beckmann and Schauenberg, 2007;Rønningen, 2007;Behaghel et al, 2014). 10 Most recently, Acemoglu and Restrepo (2018) find that robots substitute for middle-aged workers, and also provide evidence for the reverse causal direction: aging is associated with more automation across countries and also U.S. commuting zones.…”
Section: Related Literaturementioning
confidence: 99%
“…In this vein, there is also a literature that focuses on how older workers are affected by new technologies. Most confirm that older workers make less use of ICT or computers (Friedberg, 2003;Schleife, 2006;de Koning and Gelderblom, 2006), but evidence on how their labor market outcomes are affected is mixed (Borghans and ter Weel, 2002;Aubert et al, 2006;Schleife, 2006;Beckmann and Schauenberg, 2007;Rønningen, 2007;Behaghel et al, 2014). 10 Most recently, Acemoglu and Restrepo (2018) find that robots substitute for middle-aged workers, and also provide evidence for the reverse causal direction: aging is associated with more automation across countries and also U.S. commuting zones.…”
Section: Related Literaturementioning
confidence: 99%
“…Using rich employee-employer data for Norway, Haegeland et al (2007) reported that a firm's investment in new equipment and the introduction of new process technology increases the likelihood of early retirement by its employees. Other studies also found that the wage bill share of older workers is negatively correlated with the adoption of new technologies like ICT (Beckmann, 2007;Behaghel et al, 2014, Peng et al, 2017. On the other hand, technological change boosts productivity and thus wage levels, thereby encouraging older workers to remain in their jobs.…”
Section: Technology-induced Early Retirement and Its Interaction With Institutionsmentioning
confidence: 97%
“…The first objective of this article is to estimate the impact of workers' competencies on labour market opportunities. However, the acquisition of competencies is a cumulative process and skills can be acquired via different channels, not only formal education (Behaghel, Caroli, & Roger, ; OECD, ). Individual and family characteristics play a role in this process and, consequently, the distribution of these characteristics has an impact on the final distribution of competencies.…”
Section: Education Skills and Labour Market Outcomesmentioning
confidence: 99%